IRAC's Insecticide Mode of Action Classification - Frederick M. Fishel (EDIS)
Revised! PI-83, a 5-page guide by Frederic M. Fishel, explains the rationale behind the Insecticide Resistance Action Committee’s (IRAC) insecticide and acaricide mode-of-action classification. It provides a listing of those insecticide common names with their groupings and primary modes of action for insecticides currently registered in Florida. Includes sources of additional infomation. Published by the UF Pesticide Information Office, December 2008.